Characterization of Hepatitis C Virus Genotypes by Direct Sequencing of HCV 5′UTR Region of Isolates from Saudi Arabia - Shier, Medhat K. (Public Library of Science, 2014)
The current study was designed to determine the Hepatitis C Virus (HCV) genotypes in a representative sample of HCV chronically infected patients in Saudi Arabia. All HCV isolates were genotyped by sequencing of the 5′UTR region and newly identified HCV isolates were identified. Specific universal primers targeting 5′UTR region were used for both amplification and sequencing of all isolates that resulted in 244 bp fragment which represent about 80% of 5′UTR region. Most of HCV isolates in this study were genotype 4 (76.4%) where only few isolates were recognized as genotype 1 (19.6%). All results were compared to HCV reference sequences from LOS ALAMOS HCV database, considering only the complete full genomes for the main phylogenetic analysis. Sequences that showed maximum identity (98% –100%) were selected. Most isolates were identical with HCV genotype 4 references. Some isolates were similar to different subtypes of HCV genotypes 4, 1 and 6. Phylogenetic analysis showed resemblance of most isolates to similar ones from the Far East, North America and Egypt. Using sequence Weblogo, Alignment analysis of isolated HCV genotypes 4 and 1 showed 92% and 95.5% nucleotide conservation, respectively. There was no predominant nucleotide in the varied sites, in both genotypes. All isolated sequences were submitted to GenBank database.